2004
DOI: 10.5194/nhess-4-315-2004
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic high-resolution forecast of heavy precipitation over Central Europe

Abstract: Abstract. The limited-area ensemble prediction system COSMO-LEPS has been running operationally at ECMWF since November 2002. Five runs of the non-hydrostatic limited-area model Lokal Modell (LM) are available every day, nested on five selected members of three consecutive 12-h lagged ECMWF global ensembles. The limited-area ensemble forecasts range up to 120 h and LM-based probabilistic products are disseminated to several national weather services. COSMO-LEPS has been constructed in order to have a probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…In the above mentioned references and in Marsigli et al (2004), it has been shown that, over a number of test cases and for several forecast ranges (48-120 h), LEPS (the early experimental system) and COSMO-LEPS (the real-time quasi-operational system) have shown better performance than EPS for the quantitative forecast of intense precipitation, as well as the geographical localisation of the regions most likely to be affected by the flood events. Then, as regards severe precipitation events, the impact the high-resolution within a probabilistic system seems to be positive.…”
Section: The Cosmo-leps Operational Systemmentioning
confidence: 99%
“…In the above mentioned references and in Marsigli et al (2004), it has been shown that, over a number of test cases and for several forecast ranges (48-120 h), LEPS (the early experimental system) and COSMO-LEPS (the real-time quasi-operational system) have shown better performance than EPS for the quantitative forecast of intense precipitation, as well as the geographical localisation of the regions most likely to be affected by the flood events. Then, as regards severe precipitation events, the impact the high-resolution within a probabilistic system seems to be positive.…”
Section: The Cosmo-leps Operational Systemmentioning
confidence: 99%
“…Marsigli et al, 2004;Hohenegger et al, 2008;Leoncini et al, 2010;van Weverberg et al, 2010;Yussouf and Stensrud, 2011). The scope of the present study is to compare the uncertainties arising from two classes of forecast model uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, despite the computational expense, experimentation with convective-scale ensembles is already well under way (e.g. Marsigli et al, 2004;Hohenegger et al, 2008;Leoncini et al, 2010) even while the operational use of a single forecast at these resolutions remains in its infancy. At the Met Office, for example, a convective-scale model has been run routinely since 2009 and a test system for ensembles at this scale is currently being built with the intention of trialling it during the spring of 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The development of shortrange limited-area ensemble prediction systems with grid spacings of order 10 km has proved useful for quantitative precipitation forecasting (QPF) (e.g. Marsigli et al, 2004Marsigli et al, , 2005 and has therefore resulted in a movement towards convective-scale ensembles at O(1 km) grid spacing (e.g. Kong et al, 2006Kong et al, , 2007Hohenegger et al, 2008;Clark et al, 2010;Leoncini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%